Possible Sustainable Measures to Recover the Tourism Sector after the COVID-19 Crisis - Porto Bonacci, Luca; Anwar, Fahad (Journal of Public Governance, 2021)
Objectives: The objective of the present contribution is to identify and propose measures that could constitute a starting point for the governance of many tourist destinations, making it possible to revive the tourism sector, which is in a deep crisis due to the spread of COVID-19. Research Design & Methods: The paper includes both local and global analysis, and pays special attention to important Italian tourist destinations. The destinations chosen for case studies are: Lake Como, Langhe Roero Monferrato, and Amalfi Coast. The study starts with the history of the Italian tourism and then focuses on the recent trends, the best practices around the globe, and the opinions of different stakeholders of three selected territories. The analysis and evaluation of the best practices aims at identifying and proposing some replicable models and strategies that would further improve the tourism sector. Findings: Tourism is an already well-consolidated sector and consists of the exchanges and consumption of goods and services. For this reason, it is also susceptible to various changes. In some countries, the organisation of the tourism supply chain had always been fraught with many difficulties. Since the arrival of the pandemic, it has been challenged even more. It is estimated that the real damages will be quantifiable in a few years, when, hopefully, COVID-19 will no longer be a threat. Implications / Recommendations: The research shows that the academic sector and public governance should actquickly in order to seek appropriate and useful solutions and concrete proposals for safe travel, as well as help recover the tourism industry after the crisis. In this regard, a collaboration between different stakeholders in the tourism sector could be particularly helpful. Contribution / Value Added: In order to mitigate the disastrous effects of COVID-19 in the tourism sector, somemeasures have been proposed. The research is based on a multidisciplinary approach focusing on planning, business management, tourism governance, and the sociological impact.